2020
DOI: 10.1186/s10194-020-01165-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the presence of headache in hospitalized COVID-19 patients and impact on prognosis: a retrospective cohort study

Abstract: Introduction: Headache is one of the most frequent neurologic manifestations in COVID-19. We aimed to analyze which symptoms and laboratory abnormalities were associated with the presence of headache and to evaluate if patients with headache had a higher adjusted in-hospital risk of mortality. Methods: Retrospective cohort study. We included all consecutive patients admitted to the Hospital with confirmed SARS-CoV-2 infection between March 8th and April 11th, 2020. We collected demographic data, clinical varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
144
5
18

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(186 citation statements)
references
References 38 publications
19
144
5
18
Order By: Relevance
“…Patients with these complaints presented a significantly higher frequency of headache and these symptoms had a close temporal relationship, mostly occurring at the beginning of the symptomatic phase of COVID-19. Another study also found a higher frequency of headaches amongst those who had anosmia (20). Most neurological symptoms are likely to occur in the early stages of the disease with a median of 1–2 days, as cited in a recent review (18).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Patients with these complaints presented a significantly higher frequency of headache and these symptoms had a close temporal relationship, mostly occurring at the beginning of the symptomatic phase of COVID-19. Another study also found a higher frequency of headaches amongst those who had anosmia (20). Most neurological symptoms are likely to occur in the early stages of the disease with a median of 1–2 days, as cited in a recent review (18).…”
Section: Discussionmentioning
confidence: 89%
“…Three studies that assessed neurological symptoms in patients admitted with COVID-19 reported higher frequencies of headache (27% (10), 39% (19) and 43% (9)). A retrospective cohort study that assessed the prognostic value of headache concerning mortality found a headache frequency of 24% (20). One European multicenter study that assessed symptoms of patients hospitalized with COVID-19 reported a frequency of headache similar to that of the present study (70%) (21).…”
Section: Discussionmentioning
confidence: 99%
“…In total, 78 studies were included to calculate the prevalence of headache in COVID-19 and all studies were published in 2020. The studies were conducted in Brazil 50 , China 13,51-96 , Egypt 97 , France 98-101 , Germany 102 , India 103,104 , Italy [105][106][107][108][109][110][111] , Japan 112,113 , Jordan 114 , Somalia 115 , South Korea 116,117 , Spain 118,119 , Turkey 120,121 , and the US [122][123][124][125][126] . Two studies were cross-sectional 119,122 , five were prospective cohort studies 65,90,98,110,121 and the remaining 71 studies were retrospective studies.…”
Section: Study Eligibility Resultsmentioning
confidence: 99%
“…It can appear as the first symptom in meningeal involvement in these cases. Presence of headache was linked to other central nervous system (CNS) manifestations in patients with COVID-19, suggesting that it is also a CNS-associated infectious disease (13). Headache in patients with COVID-19 does not seem to have any particular characteristics, as it is described as tension-type headache or migraine without aura (14)-the two most frequently observed types of headache (12), or a migraine-like headache type (15,16).…”
Section: Introductionmentioning
confidence: 99%